Time-saver details for store planning and design - Broudy, Charles E.; Barr, Vilma (New York : McGraw Hill Education, 1995)
This sourcebook contains hundreds of standardized graphic design details and specifications for retail store and display design. From standard shelving to merchandise display units to lighting details and customized cabinetwork, from apparel shops to discount stores to supermarkets, it's packed with smart advice, hard-to-find information, and such invaluable features as: Design techniques for all store components--display structures, interior finishes, architectural elements, and more--Precise graphic details, with standard dimensioning and specifications--Generic floor plans and store layouts for 20 major store types--Types and Guidelines to make planning faster and more accurate-- Vivid photographs of store interiors and vignettes. For every aspect of store planning and design, here's the one resource you'll need to take on projects in this exciting expansive field.
Keywords: STORES, RETAIL